Answer:
It is a 14-gon.
Step-by-step explanation:
Sum of internal angles of an n sided polygon = 180(n - 2) degrees.
2160 = 180(n - 2)
2160 = 180n - 360
`180n = 2520
n = 2520 / 180
= 14.
Answer:
12-gon
Step-by-step explanation:
This means that √5 is between (4 and 9, 2 and 3, 4 and 6, square root of 2 and square root of 3).
So, √65 is between (6 x 2, 6 x 3, 6 x 4) and (6 x 3, 6 x 6, 6 x 9).
Thank you and please help me!
Part A
4 < 5 < 9 is given to us. Apply the square root to each term to end up with this inequality: sqrt(4) < sqrt(5) < sqrt(9)
So sqrt(5) is between sqrt(4) and sqrt(9)
-------------------
Part B
Simplify those two mentioned square roots
sqrt(4) = sqrt(2^2) = 2
sqrt(9) = sqrt(3^2) = 3
Therefore, sqrt(5) is also between 2 and 3
We can see this through using a calculator: sqrt(5) = 2.23607 approximately
-----------------
Part C
We can now say:
2 < sqrt(5) < 3
Multiply all three sides by 6
6*2 < 6*sqrt(5) < 6*3
So the expression 6*sqrt(5) is between 6 x 2 and 6 x 3
Sure enough, a calculator confirms this
6*sqrt(5) = 13.416408
since 6*2 = 12 and 6*3 = 18. We see that 13.416 is between 12 and 18.
write how is it done plz
Integers are numbers like ...-3, -2, -1, 0, 1, 2, 3... and so on. So, according to this definition, let's solve this problem:
28. We know that the product of three integers is -3. So, the statement states that we have three factor, so:
a.b.c = -3
The possible values of the factors are:
(3)(1)(-1) = -3
(-3)(1)(1) = -3
29. In this problem we know two nonzero integers, that is, they cannot be equal to zero. Thus, they must have different sign, that is, one of them must be positive and the other negative.For instance:
(-9)(2) = -18, So -18 is less than -9 and 2
Another example:
(1)(-8) = -8, So -8 is equal to -8 and -8 is less than 1.
30. The sign of the product of two integers with the same sign is positive, that is:
(+)(+) = (+) and
(-)(-) = (+)
So, the sign of the product of three integers with the same sign are two options:
(+)(+)(+) = (+), So the sign of the product is positive
(-)(-)(-) = (-), So the sign of the product is negative.
This option two gives us that result because:
(-)(-) = (+) and (+)(-) = (-)
7g - 12 = 3 + 7/3g